Property Management Practices Implementation and Cost Measures Efficiency in the City Government of Calamba: Basis for Action Plan - Dela Cruz, Maria Lorena (Journal of Interdisciplinary Perspectives, 2024)
The focus of this study was to assess the implementation of property management practices and efficiency of cost measures in the City Government of Calamba, aiming to provide insights into key areas of concern and potential strategies for improvement. The study employed a descriptive correlational approach, combining quantitative analysis of stakeholder perceptions. Data were collected using a researcher made questionnaire through paper surveys and google forms with 134 respondents, consisting of 20 heads and 114 employees from the office concerned with the implementation of property management practices in the City Government of Calamba. For the treatment of quantitative data, the mean and four-point likerts scale, paired t-test, the pearson product moment correleation coefficient and multiple linear regression analysis was used. The analysis revealed that first, the level of implementation of property management practices varied across different areas, with planning, acquisition, and utilization demonstrating robust implementation, while maintenance and disposal of public assets exhibited areas for improvement. Second, the assessment of cost measures efficiency reflected generally high, particularly in funding allocation and technology although skilled personnel needs enhancements. Third, the absence of significant differences in assessment between heads and employees underscored organizational cohesion and alignment of perspectives. Fourth, a significant relationship between property management practices and cost measures highlighted their interconnectedness and the importance of a holistic approach to organizational management. Based on the findings, an action plan to entitles, “Strengthening the Property Management Practices and Promoting Cost Efficiency in the City Government of Calamba” was proposed to address the areas of concern in the City Government of Calamba, improve its overall property management practices and enhance cost measures efficiency, ultimately leading to more effective and sustainable governance.